Training manual on people's biodiversity register : "jal jangal jamin register" : bio-diversity conservation and livelihood security through people's participation - Bhattacharya, A K; Bhattacharya, Ajoy Kumar, 1955- (New Delhi : Concept Pub. Co., 2005)
In the Indian context; contributed articles
Includes bibliographical references (p. [783]-814) and index.
Keywords: Forests and forestry -- India